Design and Calibration Techniques for a Multichannel FPGA-Based Time-to-Digital Converter in an Object Positioning System - Choi, Kyu Jin; Jee, Dong Woo (IEEE Transactions on Instrumentation and Measurement, 2021)
A multichannel field-programmable gate array (FPGA)-based time-to-digital converter (TDC) and its calibration techniques are presented. Herein, a frequency-tracker-based sliding-scale technique and a moving-average filter to improve the linearity and resolution are proposed. The error calibration technique automatically detects and corrects conversion errors caused by variations and mismatches in the propagation delays. The gain calibration extracts the average bin width of the fine TDC and resolves any linearity degradation in the coarse/fine interpolation architecture. The proposed techniques were applied to a four-channel TDC design implemented on a Xilinx Artix-7 FPGA. The measured differential and integral nonlinearities of all channels were within 0.51 least significant bit of 4.88 ps. The root-mean-squared resolution of the output code was 2.90-8.03 ps across a wide input range of 350 μ s.
Keywords: Calibration techniques; Integral nonlinearity; Least significant bits; Linearity degradation; Moving average filter; Positioning system; Propagation delays; Time to digital converters; Artix-7 FPGA; calibration techniques; field-programmable gate array (FPGA); moving average (MA) filter; object positioning; sliding scale; target localization; time-difference of arrival (TDOA); time-to-digital converter (TDC)